UAV-based optical imagery, digital elevation models and hillshades of Dos Lenguas rock glacier / Argentinean Dry Andes (30S, 69W; 2016, 2018, 2022, 2024) and daily static optical imagery (2023-2024) - Melanie Stammler; Jan Henrik Blöthe; Fabian Flöck; Rainer Bell; Lothar Schrott (PANGAEA, 2025)
This dataset spans UAV-based optical imagery for Dos Lenguas rock glacier in the Dry Andes of Argentina (30S and 69W) for the austral summers of 2016, 2018, 2022 and 2024; the DGNSS measurements used for georeferencing, the DEMs (11cm resolution) generated based on the UAV data, and hillshades (25cm resolution), also based on the flight campaigns. The datasets cover the surface and slopes of Dos Lenguas rock glacier (length, width, size: 1500m, 500m, approx. 0.35km^2) together with surrounding stable terrain. The imagery was collected with a DJI Phantom 3 Advanced in 2D mode (2016, 2018) and a DJI Phantom 4 RTK in terrain awareness mode (TA mode; 2022, 2024). DEMs are generated in Agisoft Metashape Professional (version 2.0.4) and georeferenced with DGNSS measurements. All DEMs are resampled to the dataset with lowest resolution (2016, 11cm). Hillshades are obtained in ArcGIS (version 10.7.1) at a resolution of 25cm. The dataset also includes daily repeated static optical imagery taken with SESACAM Plus Pro cameras at two locations in Agua Negra catchment where Dos Lenguas rock glacier is located, covering approximately 1 year (Feb 2023-Feb 2024). While the UAV datasets allow for a detailed investigation of rock glacier kinematics and for method-oriented comparisons with other remotely sensed data alike, the daily static imagery can, for example, provide insight in snow conditions; helpful for the interpretation of Dos Lenguas rock glacier kinematics.